The Alzheimer's-related amyloid beta peptide is internalised by R28 neuroretinal cells and disrupts the microtubule associated protein 2 (MAP-2) - Taylor-Walker, George (Exp Eye Res, 2016)
Age-related Macular Degeneration (AMD) is a common, irreversible blinding condition that leads to the loss of central vision. AMD has a complex aetiology with both genetic as well as environmental risks factors, and share many similarities with Alzheimer's disease. Recent findings have contributed significantly to unravelling its genetic architecture that is yet to be matched by molecular insights. Studies are made more challenging by observations that aged and AMD retinas accumulate the highly pathogenic Alzheimer's-related Amyloid beta (Aβ) group of peptides, for which there appears to be no clear genetic basis. Analyses of human donor and animal eyes have identified retinal Aβ aggregates in retinal ganglion cells (RGC), the inner nuclear layer, photoreceptors as well as the retinal pigment epithelium. Aβ is also a major drusen constituent; found correlated with elevated drusen-load and age, with a propensity to aggregate in retinas of advanced AMD. Despite this evidence, how such a potent driver of neurodegeneration might impair the neuroretina remains incompletely understood, and studies into this important aspect of retinopathy remains limited. In order to address this we exploited R28 rat retinal cells which due to its heterogeneous nature, offers diverse neuroretinal cell-types in which to study the molecular pathology of Aβ. R28 cells are also unaffected by problems associated with the commonly used RGC-5 immortalised cell-line, thus providing a well-established model in which to study dynamic Aβ effects at single-cell resolution. Our findings show that R28 cells express key neuronal markers calbindin, protein kinase C and the microtubule associated protein-2 (MAP-2) by confocal immunofluorescence which has not been shown before, but also calretinin which has not been reported previously. For the first time, we reveal that retinal neurons rapidly internalised Aβ(1-42), the most cytotoxic and aggregate-prone amongst the Aβ family. Furthermore, exposure to physiological amounts of Aβ(1-42) for 24 h correlated with impairment to neuronal MAP-2, a cytoskeletal protein which regulates microtubule dynamics in axons and dendrites. Disruption to MAP-2 was transient, and had recovered by 48 h, although internalised Aβ persisted as discrete puncta for as long as 72 h. To assess whether Aβ could realistically localise to living retinas to mediate such effects, we subretinally injected nanomolar levels of oligomeric Aβ(1-42) into wildtype mice. Confocal microscopy revealed the presence of focal Aβ deposits in RGC, the inner nuclear and the outer plexiform layers 8 days later, recapitulating naturally-occurring patterns of Aβ aggregation in aged retinas. Our novel findings describe how retinal neurons internalise Aβ to transiently impair MAP-2 in a hitherto unreported manner. MAP-2 dysfunction is reported in AMD retinas, and is thought to be involved in remodelling and plasticity of post-mitotic neurons. Our insights suggest a molecular pathway by which this could occur in the senescent eye leading to complex diseases such as AMD.